Characterization of PD-1 and PD-L1 Expression in Papillary Renal Cell Carcinoma: Results of a Large Multicenter Study - Erlmeier, Franziska; Steffens, Sandra; Stöhr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Ströbel, Philipp; Becker, Frank; Wülfing, Christian; Barth, Peter; Stöckle, Michael; et al. (Clinical Genitourinary Cancer, 2020)
Background: Programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) play a decisive role as prognostic markers in clear-cell renal cell carcinoma (RCC). To date, the role of PD-1/PD-L1 as a prognostic marker in papillary RCC (pRCC) remains scarce. Patients and Methods: Patients’ sample collection was a joint collaboration of the nationwide PANZAR consortium – a multicenter study. Medical history and tumor specimens were collected from 245 and 129 patients with pRCC types 1 and 2, respectively. Expression of PD-1 and PD-L1 was determined by immunohistochemistry in pRCC and tumor-infiltrating mononuclear cells. Results: Of 374 pRCC specimens, 204 type 1 and 97 type 2 were evaluable for PD-1 and PD-L1 expression analysis. In total, PD-1 and PD-L1 expression were found in 8 (4.9%) of 162 and 12 (7.2%) of 166 evaluable pRCC type 1 specimens. Comparably, PD-1 and PD-L1 expression were found in 2 (2.4%) of 83 and 5 (6.2%) of 81 evaluable pRCC type 2 specimens. Hardly any clinically relevant associations between PD-1 and PD-L1 positivity and clinicopathologic or clinical courses were observed, neither in pRCC type 1 nor type 2. Conclusion: The analysis of a large pRCC cohort from a multicenter consortium revealed no impact of PD-1/PD-L1 expression on prognosis in patients with pRCC with predominantly limited disease status, neither for type 1 nor type 2. However, the impact of PD-1 and PD-L1 in more advanced pRCC disease needs further elucidation. Understanding the impact of programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) expression becomes increasingly important in renal cell carcinoma (RCC) owing to increasing therapeutic implications. However, little is known in non–clear-cell RCC about the relevance of those immune checkpoint surrogates. Here, we suggest that PD-1/PD-L1 expression in papillary RCC does not have prognostic impact, neither for type 1 nor type 2. However, in advanced disease, further evaluation according to PD-1/PD-L1 is warranted.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Non-clear-cell-renal carcinoma; Papillary renal cell; PD-1; PD-L1; Renal cell carcinoma

Chromophobes Nierenzellkarzinom – Diagnostik und Prognostik - Erlmeier, Franziska (Pathologe, 2019)
Chromophobe renal cell carcinoma is one of four malignant kidney tumor subtypes. Due to its morphological variance in clinical pathological routine diagnostics, this subtype can cause certain difficulties. The tumor can be mistaken for more aggressive or benign tumors. In both cases the consequences of misdiagnosis regarding treatment decisions can be serious. Due to the morphological variance of the tumor, it has not yet been possible to develop a generally accepted, prognostically convincing graduation scheme. The aim is to improve the quality of diagnostics and estimation of prognosis for this subtype of tumor in order to optimize patient care.
CRIS-Team Scopus Importer:2019-11-26
Keywords: B7-H1 antigen; Diagnostic errors; Prognosis; Proto-oncogene proteins c‑met; Renal cell carcinoma

cMET: a prognostic marker in papillary renal cell carcinoma? - Erlmeier, Franziska; Bruecher, Benedict; Stoehr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Ströbel, Philipp; Becker, Frank; Wülfing, Christian; Barth, Peter; Stöckle, Michael; et al. (Human Pathology, 2022)
The tyrosine-protein kinase c-Met plays a decisive role in numerous cellular processes, as a proto-oncogene that supports aggressive tumor behavior. It is still unknown whether c-Met could be relevant for prognosis of papillary RCC (pRCC). Specimen collection was a collaboration of the PANZAR consortium. Patients' medical history and tumor specimens were collected from 197 and 110 patients with type 1 and 2 pRCC, respectively. Expression of cMET was determined by immunohistochemistry. In total, cMET staining was evaluable in of 97 of 197 type 1 and 63 of 110 type 2 pRCC cases. Five-year overall survival revealed no significant difference in dependence of cMET positivity (cMET− vs. cMET+: pRCC type 1: 84.8% vs. 80.3%, respectively [p = 0.303, log-rank]; type 2: 71.4% vs. 64.4%, respectively [p = 0.239, log-rank]). Interestingly, the subgroup analyses showed a significant difference for cMET expression in T stage and metastases of the pRCC type 2 (p = 0.014, p = 0.022, chi-square). The cMET-positive type 2 collective developed more metastases than the cMET-negative cohort (pRCC type 2 M+: cMET−: 2 [4.3%] vs. cMET+: 12 [19%]). cMET expression did not qualify as a prognostic marker in pRCC for overall survival.
CRIS-Team Scopus Importer:2022-02-04
Keywords: cMET; Outcome; Papillary renal cell carcinoma; Prognosis; Survival

Correction to: Multi-institutional re-evaluation of prognostic factors in chromophobe renal cell carcinoma: proposal of a novel two-tiered grading scheme (Virchows Archiv, (2019), 10.1007/s00428-019-02710-w) - Ohashi, Riuko; Martignoni, Guido; Hartmann, Arndt; Caliò, Anna; Segala, Diego; Stöhr, Christine; Wach, Sven; Erlmeier, Franziska; Weichert, Wilko; Autenrieth, Michael; Schraml, Peter; Rupp, Niels J.; et al. (Virchows Archiv, 2020)
The legends of Figs. 1 and 3 in the published original version of the above article are incorrect.
CRIS-Team Scopus Importer:2020-03-20

Evaluation of Gas 6 as a Prognostic Marker in Papillary Renal Cell Carcinoma - Mikuteit, Marie; Zschäbitz, Stefanie; Stoehr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Ströbel, Philipp; Becker, Frank; Wülfing, Christian; Barth, Peter; Stöckle, Michael; et al. (Urologia Internationalis, 2023)
Introduction: Growth arrest-specific protein 6 (Gas 6) is a ligand that plays a role in proliferation and migration of cells. For several tumor entities, high levels of Gas 6 are associated with poorer survival. We examined the prognostic role of Gas 6 in renal cell carcinoma (RCC), especially in papillary RCC (pRCC), which is still unclear. Methods: The patients' sample collection is a joint collaboration of the PANZAR consortium. Patients' medical history and tumor specimens were collected from n = 240 and n = 128 patients with type 1 and 2 pRCC, respectively. Expression of Gas 6 was determined by immunohistochemistry. Results: In total, Gas 6 staining was evaluable in 180 of 240 type 1 and 110 of 128 type 2 pRCC cases. Kaplan-Meier analysis disclosed no significant difference in 5-year overall survival for all pRCC nor either subtype. Also, Gas+ and Gas- groups did not significantly differ in any tumor or patient characteristics. Conclusion: Gas 6 was not found to be an independent prognostic marker in pRCC. Future studies are warranted to determine if Gas 6 plays a role as prognostic marker or therapeutic target in pRCC.
CRIS-Team Scopus Importer:2023-08-11

Expression of Nectin-4 in Chromophobe Renal Cell Carcinoma in a Multicenter Cohort: Early Prognostic and Therapeutic Considerations - Mikuteit, Marie; Zschäbitz, Stefanie; Autenrieth, Michael; Weichert, Wilko; Hartmann, Arndt; Steffens, Sandra; Erlmeier, Franziska (Oncology, 2024)
Introduction: Nectin-4 is a member of the nectin family and a calcium-independent immunoglobulin-like transmembrane protein that contributes to tumor growth and angiogenesis in malignant tumors. A nectin-4-directed antibody drug conjugate, enfortumab vedotin-ejf, has recently been approved for treatment in urothelial cancer and is currently under investigation in other tumor entities such as breast, lung, and prostate cancer. In non-clear cell renal cell carcinoma (RCC), vascular endothelial growth factor (VEGF)- directed tyrosine kinase inhibitors and checkpoint inhibitors are currently treatments of choice. However, due to the rarity of disease treatment recommendations for chromophobe RCC (chRCC) are limited and new therapeutic agents urgently needed. In this study, we investigated the expression and prognostic impact of nectin-4 in a large cohort of chRCC. Methods: Patients who underwent renal surgery due to chRCC were recruited. Clinical data were retrospectively evaluated. Tumor specimen was analyzed for nectin-4 expression by immunohistochemistry. Results: Eighty-one chRCC patients were eligible for analysis. In 15 (18.5%) samples, tumors were positive for nectin-4. No significant associations were found for nectin-4 expression and clinical attributes in patients with chRCC. Kaplan-Meier analysis disclosed a 5-year overall survival for nectin-4- negative and nectin-4-positive tumors of 91.8% versus 100.0% (p = 0.316, log rank). Conclusions: In chRCC, a small subset of tumors expresses nectin-4 potentially amenable to nectin-4-directed treatment. Expression of nectin-4 is not associated with parameters of aggressiveness or survival. Due to the rare incidence of chRCC, further studies with larger cohorts are warranted.
CRIS-Team Scopus Importer:2024-06-07
Keywords: Chromophobe histology; Nectin-4; Renal cell carcinoma; Survival

Expression of nectin-4 in papillary renal cell carcinoma - Zschabitz, Stefanie; Mikuteit, Marie; Stoehr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Stroebel, Philipp; Becker, Frank; Wuelfing, Christian; Barth, Peter; Stoeckle, Michael; et al. (Discover Oncology, 2022)
Background: Nectin-4 contributes to tumor proliferation, lymphangiogenesis and angiogenesis in malignant tumors and is an emerging target in tumor therapy. In renal cell carcinoma (RCC) VEGF-directed tyrosine kinase inhibitors and checkpoint inhibitors are currently treatments of choice. Enfortumab vedotin-ejf (EV) is an antibody drug conjugate that targets Nectin-4. The aim of our study was to investigate the expression of Nectin-4 in a large cohort of papillary RCC specimens. Patients and methods: Specimens were derived from the PANZAR consortium (Erlangen, Heidelberg, Herne, Homburg, Mainz, Mannheim, Marburg, Muenster, LMU Munich, TU Munich, and Regensburg). Clinical data and tissue samples from n = 190 and n = 107 patients with type 1 and 2 pRCC, respectively, were available. Expression of Nectin-4 was determined by immunohistochemistry (IHC). Results: In total, Nectin-4 staining was moderately or strongly positive in of 92 (48.4%) of type 1 and 39 (36.4%) type 2 of pRCC cases. No associations between Nectin-4 expression and age at diagnosis, gender, grading, and TNM stage was found. 5 year overall survival rate was not statistically different in patients with Nectin-4 negative versus Nectin-4 positive tumors for the overall cohort and the pRCC type 2 subgroup, but higher in patient with Nectin-4 positive pRCC type 1 tumors compared to Nectin-4 negative tumors (81.3% vs. 67.8%, p = 0.042). Conclusion: Nectin-4 could not be confirmed as a prognostic marker in pRCC in general. Due to its high abundance on pRCC specimens Nectin-4 is an interesting target for therapeutical approaches e.g. with EV. Clinical trials are warranted to elucidate its role in the pRCC treatment landscape.
CRIS-Team Scopus Importer:2022-10-07
Keywords: Nectin 4; Papillary renal cell carcinoma

Expression of PD-1 and CTLA-4 Are Negative Prognostic Markers in Renal Cell Carcinoma - Kahlmeyer, Andreas; Stoehr, Christine; Hartmann, Arndt; Goebell, Peter; Wullich, Bernd; Wach, Sven; Taubert, Helge; Erlmeier, Franziska (Journal of Clinical Medicine, 2019)
Immuno-oncological therapy with checkpoint inhibition (CI) has become a new standard treatment in metastatic renal cell carcinoma (RCC), but the prognostic value of the expression of CI therapy target molecules is still controversial. 342 unselected consecutive RCC tumor samples were analyzed regarding their PD-1, PD-L1, and CTLA-4 expression by immunohistochemistry (IHC). The prognostic values for cancer-specific survival (CSS) and overall survival (OS) were analyzed for those not exposed to CI therapy. The expression of PD-1 in tumor-infiltrating mononuclear cells (TIMC) and PD-L1 in tumor cells was detected in 9.4% and 12.3%, respectively (Immune reactive score (IRS) > 0). Furthermore, PD-L1 expression in TIMC (IRS > 0) and CTLA-4 expression in TIMC (>1% positive cells) was detected in 4.8% and 6.3%. PD-1 expression and CTLA-4 expression were significantly associated with a worse OS and CSS in log rank survival analysis and univariate Cox regression analysis. CTLA-4 expression is a prognostic marker that is independently associated with a worse outcome in multivariate Cox regression analysis in the whole cohort (OS: p = 0.013; CSS: p = 0.048) as well as in a non-metastatic subgroup analysis (OS: p = 0.028; CSS: p = 0.022). Patients with combined CTLA-4 expression and PD-1-expression are at highest risk in OS and CSS. In RCC patients, PD-1 expression in TIMC and CTLA-4 expression in TIMC are associated with a worse OS and CSS. The combination of PD-1 expression in TIMC and CTLA-4 expression in TIMC might identify high risk patients. This is, to our knowledge, the first description of CTLA-4 expression to be a prognostic marker in RCC.
CRIS-Team WoS Importer:2019-06-25

Expression of Prostate-specific Membrane Antigen (PSMA) in Papillary Renal Cell Carcinoma - Overview and Report on a Large Multicenter Cohort - Zschaebitz, Stefanie; Erlmeier, Franziska; Stoehr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Stroebel, Philipp; Becker, Frank; Wuelfing, Christian; Barth, Peter; Stoeckle, Michael; et al. (Journal of Cancer, 2022)
Prostate specific membrane antigen (PSMA) is an emerging diagnostic and therapeutic target in prostate cancer. 68 Ga-PSMA-labeled hybrid imaging is used for the detection of prostate primary tumors and metastases. Therapeutic applications such as Lutetium-177 PSMA radionuclide therapy or bispecific antibodies that target PSMA are currently under investigation within clinical trials. The expression of PSMA, however, is not specific to prostate-tissue. It has been described in the neovascular endothelium of different types of cancer such as breast cancer, and clear cell renal cell carcinoma (ccRCC). The aim of this study was to analyze PSMA expression in papillary RCC (pRCC) type 1 and type 2, the most common non-ccRCC subtypes, and to evaluate the potential of PSMA-targeted imaging and treatment in pRCC. Formalin-fixed, paraffin-embedded tissue samples of primary tumors were analyzed for PSMA expression by immunohistochemistry. Out of n=374 pRCC specimens from the multicenter PANZAR consortium, n=197 pRCC type 1 and n=110 type 2 specimens were eligible for analysis and correlated with clinical data. In pRCC type 1 PSMA staining was positive in 4 of 197 (2.0%) samples whereas none (0/110) of the pRCC type 2 samples were positive for PSMA in this large cohort of pRCC patients. No significant PSMA expression was detected in pRCC. Reflecting current clinical evaluation of PMSA expression in RCC do not encourage further analysis in papillary subtypes.
CRIS-Team WoS Importer:2022-04-15
Keywords: prostate specific membrane antigen; papillary renal cell carcinoma; kidney cancer

Expression of Prostate-specific Membrane Antigen (PSMA) in papillary renal cell carcinoma (pRCC) - Zschaebitz, S.; Erlmeier, Franziska; Stoehr, Christine; Polifka, Iris; Schrader, A. J.; Hartmann, Arndt; Ivanyi, P.; Steffens, S. (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Growth Arrest-Specific 6 in Chromophobe Renal Cell Carcinoma - Mikuteit, Marie; Zschäbitz, Stefanie; Erlmeier, Maximilian; Autenrieth, Michael; Weichert, Wilko; Hartmann, Arndt; Steffens, Sandra; Erlmeier, Franziska (Oncology, 2022)
BACKGROUND: Overexpression of tumor-associated growth arrest-specific protein 6 (Gas6) is found in many tumor entities. The prognostic value of Gas6 in renal cell carcinoma (RCC), especially in non-clear cell RCC, is still unclear. AIM: The aim of the study was to evaluate the prognostic impact of Gas6 expression in a large cohort of patients with chromophobe RCC (chRCC). MATERIAL AND METHODS: Patients who underwent renal surgery due to chRCC were retrospectively evaluated. Tumor specimens were analyzed for Gas6 expression by immunohistochemistry. RESULTS: Eighty-one chRCC patients were eligible for analysis; of these, 24 (29.6%) patients were positive for Gas6. No significant associations were found for Gas6 expression and clinical attributes in patients with chRCC. The Kaplan-Meier analysis revealed no differences in 5-year overall survival for Gas6- compared to Gas6+ (89.6% vs. 100.0%; p = 0.288) tumors. CONCLUSION: In chRCC, Gas6 expression is not associated with survival and other parameters of aggressiveness. Due to the rare incidence of chRCC, further studies with larger cohorts are warranted.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Chromophobe histology; Growth arrest-specific protein 6; Renal cell carcinoma; Survival

Immunohistochemical expression of the hepatocyte growth factor in chromophobe renal cell carcinoma - Erlmeier, Maximilian; Mikuteit, Marie; Zschaebitz, Stefanie; Autenrieth, Michael; Weichert, Wilko; Hartmann, Arndt; Steffens, Sandra; Erlmeier, Franziska (BMC Urology, 2023)
Background: The prognostic value of Hepatocyte growth factor (HGF) in non-clear cell renal cell carcinoma (RCC) is still unclear. The aim of this study is to evaluate the prognostic impact of HGF expression in a large cohort of chromophobe RCC (chRCC). Methods: Patients who underwent renal surgery due to chRCC were recruited. Clinical data was retrospectively evaluated. Tumor specimen were analyzed for HGF expression by immunohistochemistry. Results: 81 chRCC patients were eligible for analysis, thereof 37 (45.7%) patients were positive for HGF. No significant associations were found for HGF expression and clinical attributes in patients with chRCC. Kaplan-Meier analysis revealed no differences in 5-year overall survival (OS) for patients with HGF− compared to HGF+ tumors (95.0% versus 90.9%; p = 0.410). Conclusions: In chRCC HGF expression is not associated with parameters of aggressiveness or survival.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Chromophobe histology; HGF; Renal Cell Carcinoma; Survival

In Situ Metabolomics Expands the Spectrum of Renal Tumours Positive on Tc-99(m)-sestamibi Single Photon Emission Computed Tomography/Computed Tomography Examination - Papathomas, Thomas; Tzortzakakis, Antonios; Sun, Na; Erlmeier, Franziska; Feuchtinger, Annette; Trpkov, Kiril; Bazarova, Alina; Arvanitis, Alexandros; Wang, Wanzhong; Bozoky, Bela; Kokaraki, Georgia; Axelsson, Rimma; et al. (European Urology Open Science, 2020)
Background: Definite noninvasive characterisation of renal tumours positive on Tc-99m-sestamibi single photon emission computed tomography/computed tomography (SPECT/CT) examination including renal oncocytomas (ROs), hybrid oncocytic chromophobe tumours (HOCTs), and chromophobe renal cell carcinoma (chRCC) is currently not feasible.
CRIS-Team WoS Importer:2021-01-15

MALDI Mass Spectrometry Imaging—Prognostic Pathways and Metabolites for Renal Cell Carcinomas - Erlmeier, Franziska; Sun, Na; Shen, Jian; Feuchtinger, Annette; Buck, Achim; Prade, Verena M.; Kunzke, Thomas; Schraml, Peter; Moch, Holger; Autenrieth, Michael; Weichert, Wilko; Hartmann, Arndt; et al. (Cancers, 2022)
High mass resolution matrix-assisted laser desorption/ionization (MALDI) mass spectrometry imaging (MSI) is a suitable method for biomarker detection for several tumor entities. Renal cell carcinoma (RCC) is the seventh most common cancer type and accounts for more than 80% of all renal tumors. Prognostic biomarkers for RCC are still missing. Therefore, we analyzed a large, multicenter cohort including the three most common RCC subtypes (clear cell RCC (ccRCC), papillary RCC (pRCC) and chromophobe RCC (chRCC)) by MALDI for prognostic biomarker detection. MALDI-Fourier-transform ion cyclotron resonance (FT-ICR)-MSI analysis was performed for renal carcinoma tissue sections from 782 patients. SPACiAL pipeline was integrated for automated co-registration of histological and molecular features. Kaplan–Meier analyses with overall survival as endpoint were executed to determine the metabolic features associated with clinical outcome. We detected several pathways and metabolites with prognostic power for RCC in general and also for different RCC subtypes.
CRIS-Team Scopus Importer:2022-04-15
Keywords: chromophobe renal cell carcinoma; clear-cell renal cell carcinoma; mass spectrometry imaging; metabolomics; papillary renal cell carcinoma

Mass Spectrometry Imaging Differentiates Chromophobe Renal Cell Carcinoma and Renal Oncocytoma with High Accuracy - Kriegsmann, Mark; Casadonte, Rita; Maurer, Nadine; Stoehr, Christine; Erlmeier, Franziska; Moch, Holger; Junker, Klaus; Zgorzelski, Christiane; Weichert, Wilko; Schwamborn, Kristina; Deininger, Soeren-Oliver; Gaida, Matthias; et al. (Journal of Cancer, 2020)
Background: While subtyping of the majority of malignant chromophobe renal cell carcinoma (cRCC) and benign renal oncocytoma (rO) is possible on morphology alone, additional histochemical, immunohistochemical or molecular investigations are required in a subset of cases. As currently used histochemical and immunohistological stains as well as genetic aberrations show considerable overlap in both tumors, additional techniques are required for differential diagnostics. Mass spectrometry imaging (MSI) combining the detection of multiple peptides with information about their localization in tissue may be a suitable technology to overcome this diagnostic challenge.
CRIS-Team WoS Importer:2020-09-11

Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry Imaging: Diagnostic Pathways and Metabolites for Renal Tumor Entities - Erlmeier, Franziska; Sun, Na; Shen, Jian; Feuchtinger, Annette; Buck, Achim; Prade, Verena M.; Kunzke, Thomas; Schraml, Peter; Moch, Holger; Autenrieth, Michael; Weichert, Wilko; Hartmann, Arndt; et al. (Oncology, 2023)
Background: Correct tumor subtyping of primary renal tumors is essential for treatment decision in daily routine. Most of the tumors can be classified based on morphology alone. Nevertheless, some diagnoses are difficult, and further investigations are needed for correct tumor subtyping. Besides histochemical investigations, high-mass-resolution matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI) can detect new diagnostic biomarkers and hence improve the diagnostic. Patients and Methods: Formalin-fixed paraffin embedded tissue specimens from clear cell renal cell carcinoma (ccRCC, n = 552), papillary renal cell carcinoma (pRCC, n = 122), chromophobe renal cell carcinoma (chRCC, n = 108), and renal oncocytoma (rO, n = 71) were analyzed by high-mass-resolution MALDI fourier-transform ion cyclotron resonance (FT-ICR) MSI. The SPACiAL pipeline was executed for automated co-registration of histological and molecular features. Pathway enrichment and pathway topology analysis were performed to determine significant differences between RCC subtypes. Results: We discriminated the four histological subtypes (ccRCC, pRCC, chRCC, and rO) and established the subtype-specific pathways and metabolic profiles. rO showed an enrichment of pentose phosphate, taurine and hypotaurine, glycerophospholipid, amino sugar and nucleotide sugar, fructose and mannose, glycine, serine, and threonine pathways. ChRCC is defined by enriched pathways including the amino sugar and nucleotide sugar, fructose and mannose, glycerophospholipid, taurine and hypotaurine, glycine, serine, and threonine pathways. Pyrimidine, amino sugar and nucleotide sugar, glycerophospholipids, and glutathione pathways are enriched in ccRCC. Furthermore, we detected enriched phosphatidylinositol and glycerophospholipid pathways in pRCC. Conclusion: In summary, we performed a classification system with a mean accuracy in tumor discrimination of 85.13%. Furthermore, we detected tumor-specific biomarkers for the four most common primary renal tumors by MALDI-MSI. This method is a useful tool in differential diagnosis and biomarker detection.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Chromophobe renal cell carcinoma; Clear cell renal cell carcinoma; Mass spectrometry imaging; Metabolomics; Papillary renal cell carcinoma; Renal oncocytoma

Multi-institutional re-evaluation of prognostic factors in chromophobe renal cell carcinoma: proposal of a novel two-tiered grading scheme - Ohashi, Riuko; Martignoni, Guido; Hartmann, Arndt; Caliò, Anna; Segala, Diego; Stöhr, Christine; Wach, Sven; Erlmeier, Franziska; Weichert, Wilko; Autenrieth, Michael; Schraml, Peter; Rupp, Niels J.; et al. (Virchows Archiv, 2019)
A histological grading system of chromophobe renal cell carcinoma (chRCC) is highly desirable to identify approximately 5–10% of tumors at risk for progression. Validation studies failed to demonstrate a correlation between the four-tiered WHO/ISUP grade and outcome. Previous proposals with three-tiered chromophobe grading systems could not be validated. In this study, the presence of sarcomatoid differentiation, necrosis, and mitosis was analyzed in a Swiss cohort (n = 42), an Italian cohort (n = 103), a German cohort (n = 54), a Japanese cohort (n = 119), and The Cancer Genome Atlas cohort (n = 64). All 3 histological parameters were significantly associated with shorter time to tumor progression and overall survival in univariate analysis. Interobserver variability for identification of these parameters was measured by Krippendorff’s alpha coefficient and showed high concordance for the identification of sarcomatoid differentiation and tumor necrosis, but only low to medium concordance for the identification of mitosis. Therefore, we tested a two-tiered tumor grading system (low versus high grade) based only on the presence of sarcomatoid differentiation and/or necrosis finding in the combined cohorts (n = 382). pT stage, patient’s age (> 65 vs ≤ 65), lymph node and/or distant metastasis, and the two-tiered grading system (low versus high grade) were significantly associated with overall survival and were independent prognostic parameters in multivariate analysis (Cox proportional hazard). This multi-institutional evaluation of prognostic parameters suggests tumor necrosis and sarcomatoid differentiation as reproducible components of a two-tiered chromophobe tumor grading system.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Chromophobe renal cell carcinoma; Kidney; Mitosis; Necrosis; Prognosis; Sarcomatoid differentiation; The Cancer Genome Atlas (TCGA); Tumor grade

Pathology and molecular pathology of renal cell cancer Pathologie und Molekularpathologie des Nierenzellkarzinoms - Erlmeier, Franziska; Agaimy, Abbas; Hartmann, Arndt; Stöhr, Christine G. (Onkologe, 2019)
Background: The latest edition of the WHO classification of urogenital tumors was published in January 2016. Numerous innovations have been included following the decisions of the consensus conference held in Zurich in March 2015. This review article presents the histopathology and molecular pathology of renal tumors defined in the 2016 WHO classification. Results and conclusions: In recent years knowledge about the morphology and the biological behavior of kidney tumors has steadily improved. In particular, the expanded molecular knowledge and improved data from clinicopathological studies of these tumors have led to the recognition of new entities by the WHO. These include, among others, succinate dehydrogenase B deficiency-associated renal cell carcinoma, hereditary leiomyomatosis-associated renal cell cancer, tubulocystic renal cell carcinoma and clear cell papillary renal cell carcinoma.
CRIS-Team Scopus Importer:2019-05-24
Keywords: Aberration; chromosomal; Mutation; Subtype; Urogenital tumors; WHO classification

Spatial Immunephenotypes of Distant Metastases but not Matched Primary Urothelial Carcinomas Predict Response to Immune Checkpoint Inhibition - Erlmeier, Franziska; Klümper, Niklas; Landgraf, Laura; Strissel, Pamela; Strick, Reiner; Sikic, Danijel; Taubert, Helge; Wach, Sven; Geppert, Carol-Immanuel; Bahlinger, Veronika; Breyer, Johannes; Ritter, Manuel; et al. (European Urology, 2022)
Background: The value of programmed cell death ligand-1 (PD-L1) to predict durable responses to immune checkpoint inhibitors (ICIs) in metastatic urothelial carcinoma (mUC) is inconsistent. We hypothesize that the use of archived primary tumor material (PRIM) for PD-L1 testing in clinical trials not properly reflecting the metastatic disease status (MET) contributes to this clinical issue. Objective: To analyze the predictive and prognostic value of PD-L1, spatial immunephenotypes, and major histocompatibility complex class I (MHC-I) determined in patient-matched PRIM/MET. Design, setting, and participants: PD-L1, spatial immunephenotypes, and MHC-I were examined in 154 mUC patients with at least one available pretreatment MET (138 patient-matched PRIM/MET pairs). Outcome measurements and statistical analysis: PD-L1, spatial immunephenotype, and MHC-I status of (patient-matched PRIM and) pretreatment MET were correlated with chemotherapy and ICI response and outcomes. Results and limitations: Discordance rates in patient-matched PRIM/MET were 25/30%, 36%, and 49% for PD-L1 (CPS10/IC5%), immunephenotypes, and MHC-I (loss vs preserved), respectively. Correlations with chemotherapy and ICI responses were observed for immunephenotypes and MHC-I status determined in MET (not for PD-L1 alone), but not in PRIM. In case of ICIs, patients with cytotoxic tumor immune microenvironment (TIME) showed durable responses with disease control rates of 90% and a hazard ratio for disease progression/death of 0.05 (95% confidence interval: 0.01–0.65) versus patients with immunedepleted MET (disease control rate 29%). MET MHC-I status added an incremental value to predict durable ICI responses. Limitations include the partly retrospective design and the lack of MET multisampling on individual patient level. Conclusions: The TIME is subject to substantial dynamics during metastatic evolution. MET immunephenotypes and MHC-I statuses show promising potential to predict chemotherapy and durable ICI responses, while the PRIM TIME does not. Thus, future clinical trials should rather rely on pretreatment MET biopsies reflecting the current immunological disease state than on PRIM. Patient summary: Prediction of chemotherapy and responses to immune checkpoint inhibitors might be possible using representative pretreatment metastatic biopsies.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Immune microenvironment; Immune therapy; Metastatic urothelial cancer; Subtypes; Urothelial cancer

The prognostic impact of Claudin 6 in papillary renal cell carcinoma - Mikuteit, Marie; Zschäbitz, Stefanie; Stöhr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Ströbel, Philipp; Becker, Frank; Wülfing, Christian; Barth, Peter; Stöckle, Michael; et al. (Pathology Research and Practice, 2022)
Background: Claudins are promising biomarkers for diagnosis and prognosis or targets for treatment. They play a major role in signal transduction and are important in nearly all aspects of tumorigenesis. Claudin 6 is a member of the claudin family and is part of the tight junction molecule. It is reactivated in several cancer types and serves as prognostic marker in, for example, gastric, breast or non small cell lung cancer. The prognostic role of Claudin 6 in renal cell carcinoma (RCC), especially in papillary RCC (pRCC), is still unclear. Patients and Methods: The patients’ sample collection was a joint collaboration of the PANZAR consortium. Patients’ medical history and tumor specimens were collected from n = 240 and n = 128 patients with type 1 and 2 pRCC, respectively. Expression of Claudin 6 was determined by immunohistochemistry. Results: In total, Claudin 6 staining was positive in 55 of 240 type 1 and 30 of 128 type 2 pRCC cases. Kaplan-Meier analysis disclosed an overall survival of 84% for Claudin 6- compared to 78% for Claudin 6 + in pRCC type 1 tumors (p = 0.449, log-rank) and 68% for Claudin 6- compared to 65.4% for Claudin 6 + in pRCC type 2 tumors (p = 0.364, log-rank). Conclusion: In this study, claudin 6 expression showed no significant association regarding overall survival (OS) and therefore did not qualify as a prognostic marker in pRCC. Future studies will have to determine, whether Claudin 6 plays a prognostic role in other RCC entities. In addition, the function of Claudin 6 as a predictive marker for therapeutic approaches has to be evaluated in future studies.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Claudin 6; Papillary renal cell carcinoma; Prognosis; Survival

The Prognostic Impact of PD-L2 in Papillary Renal-Cell Carcinoma. - Mondorf, Yvonne; Mikuteit, Marie; Ivanyi, Philipp; Stoehr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Stroebel, Philipp; Becker, Frank; Wuelfing, Christian; Barth, Peter; et al. (Urologia Internationalis, 2022)
INTRODUCTION: Programmed death-1 ligand (PD-L1) has been often studied in different types of renal-cell carcinoma (RCC). For example, in clear-cell renal carcinoma it is well established that programmed death-1 receptor and PD-L1 are important prognostic markers. In contrast, the role of programmed death-2 ligand (PD-L2) as prognostic marker remains unclear. The aim of this study was to evaluate if PD-L2 expression could play a role as a prognostic marker for papillary RCC (pRCC). METHODS: The patients' sample collection was a joint collaboration of the PANZAR consortium. Patients' medical history and tumor specimens were collected from n = 240 and n = 128 patients with type 1 and 2 pRCC, respectively. Expression of PD-L2 was determined by immunohistochemistry. In total, PD-L2 staining was evaluable in 185 of 240 type 1 and 99 of 128 type 2 pRCC cases. RESULTS: PD-L2 staining was positive in 67 (36.2%) of type 1 and in 31 (31.3%) of type 2 pRCC specimens. The prevalence of PD-L2+ cells was significantly higher in high-grade type 1 tumors (p = 0.019) and in type 2 patients with metastasis (p = 0.002). Kaplan-Meier analysis disclosed significant differences in 5-year overall survival (OS) for patients with PD-L2- compared to PD-L2+ in pRCC type 1 of 88.4% compared to 73.6% (p = 0.039) and type 2 of 78.8% compared to 39.1% % (p < 0.001). However, multivariate analysis did not identify the presence of PD-L2+ cells neither in type 1 nor type 2 pRCC as an independent predictor of poor OS. DISCUSSION/CONCLUSION: PD-L2 expression did not qualify as an independent prognostic marker in pRCC. Future studies will have to determine whether anti-PD-L2-targeted treatment may play a role in pRCC and expression can potentially serve as a predictive marker for these therapeutic approaches.
EVALuna2:505682

The role of claudin-6 in chromophobe renal cell carcinoma - Erlmeier, Franziska; Zschäbitz, Stefanie; Mikuteit, Marie; Autenrieth, Michael; Weichert, Wilko; Hartmann, Arndt; Steffens, Sandra (Histology and Histopathology, 2023)
BACKGROUND: The prognostic value of Claudin-6 (CLDN6) in non clear cell renal cell carcinoma (RCC) is still unclear. AIM: To evaluate the prognostic impact of CLDN6 expression in a large cohort of chromophobe RCC (chRCC). MATERIAL AND METHODS: Patients who underwent renal surgery due to chRCC were recruited. Clinical data were retrospectively evaluated. Tumor specimens were analyzed for CLDN6 expression by immunohistochemistry. RESULTS: 81 chRCC patients were eligible for analysis, thereof 10 (12.3%) patients were positive for CLDN6. No significant associations were found for CLDN6 expression and clinical attributes in patients with chRCC. Kaplan-Meier analysis revealed no differences in overall survival (OS) for patients with CLDN6⁻ compared to CLDN6⁺ tumors (87.0% versus 62.5%; p=0.174). CONCLUSION: In chRCC CLDN6 expression is not associated with parameters of aggressiveness or survival. Due to the rare incidence of chRCC further studies with larger cohorts are warranted.
CRIS-Team Scopus Importer:2023-04-14

The synergism of spatial metabolomics and morphometry improves machine learning-based renal tumour subtype classification. - Prade, Verena M.; Sun, Na; Shen, Jian; Feuchtinger, Annette; Kunzke, Thomas; Buck, Achim; Schraml, Peter; Moch, Holger; Schwamborn, Kristina; Autenrieth, Michael; Gschwend, Jurgen E.; Erlmeier, Franziska; et al. (Clinical and Translational Medicine, 2022)
EVALuna2:536086

Trophoblast Cell Surface Antigen 2 (Trop2) in Chromophobe Renal Cell Carcinoma - Mikuteit, Marie; Steffens, Sandra; Zschäbitz, Stefanie; Autenrieth, Michael; Weichert, Wilko; Hartmann, Arndt; Erlmeier, Franziska (Oncology, 2022)
BACKGROUND: Overexpression of tumor-associated calcium signal transducer 2 (Trop2) is found in many tumor entities. The prognostic value of Trop2 in renal cell renal carcinoma (RCC), especially in nonclear cell RCC, is still unclear. AIM: The aim of this study was to evaluate the prognostic impact of Trop2 expression in a large cohort of patients with chromophobe (ch)RCC. MATERIALS AND METHODS: Patients who underwent renal surgery due to chRCC were retrospectively evaluated. Tumor specimens were analyzed for Trop2 expression by immunohistochemistry. RESULTS: Eighty-one chRCC patients were eligible for analysis, of these 24 (29.6%) patients were positive for Trop2. No significant associations were found for Trop2 expression and clinical attributes in patients with chRCC. The Kaplan-Meier analysis revealed no differences in 5-year overall survival for Trop2- compared to Trop2+ (89.6% vs. 100.0%; p = 0.288). CONCLUSION: In chRCC, Trop2 expression is not associated with survival and other parameters of aggressiveness. Due to the rare incidence of chRCC, further studies with larger cohorts are warranted.
CRIS-Team Scopus Importer:2022-06-10
Keywords: Chromophobe histology; Renal cell carcinoma; Survival; Trophoblast cell surface antigen 2

Tumour immune microenvironment drives prognostic relevance correlating with bladder cancer subtypes - Eckstein, Markus; Strissel, Pamela; Pfannstiel, C.; Chiappinelli, K.; Sikic, D.; Wach, S.; Taubert, Helge; Wullich, Bernd; Keck, Bastian; Wirtz, R.; Breyer, J.; Burger, M.; et al. (VIRCHOWS ARCHIV, 2019)
CRIS-Team WoS Importer:2019-09-27